Effect of Lemon Aromatherapy on Sleep Quality among Third-Trimester Pregnant Women: A Pre-Experimental Study - Suci Nanda Resti Tarigan; Friska Margaret Parapat; Elisa Silvia Aritonang (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Sleep disturbances are commonly experienced by pregnant women during the third trimester due to physiological, hormonal, and psychological changes. Poor sleep quality during late pregnancy may increase the risk of adverse maternal and fetal outcomes, including hypertension, fatigue, and complications during delivery. Non-pharmacological interventions are recommended to manage sleep problems during pregnancy because pharmacological therapies may pose potential risks to the fetus. Aromatherapy using lemon essential oil (Citrus limon) is considered a safe complementary therapy that may promote relaxation and improve sleep quality. This study aimed to analyze the effect of lemon aromatherapy on sleep quality among third-trimester pregnant women. Research Methodology: This study employed a quasi-experimental design with a one-group pretest–posttest approach. The research was conducted at PMB Theresia Anggraini Medan Deli from January to April 2025. A total of 30 pregnant women in the third trimester were recruited using total sampling. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). Participants received lemon aromatherapy inhalation for approximately 15 minutes before bedtime for seven consecutive days. Data were analyzed using descriptive statistics and paired statistical tests to compare sleep quality before and after the intervention with a significance level of 0.05. Results: The findings indicated an improvement in sleep quality following the aromatherapy intervention. Before the intervention, all participants experienced poor sleep quality. After receiving lemon aromatherapy, most participants reported improved sleep patterns characterized by easier sleep initiation, reduced nighttime awakening, and greater feelings of relaxation before sleep. The statistical analysis demonstrated a significant improvement in sleep quality after the intervention. Conclusion: Lemon aromatherapy may serve as a safe, simple, and accessible complementary intervention to improve sleep quality among pregnant women in the third trimester. Integrating aromatherapy into routine antenatal care may support maternal comfort and contribute to holistic maternal health services.